Positive Psychotherapy tools in groups - Arno Remmers (The Global Psychotherapist)
In Positive group therapy, certain tools can be used to moderate and guide the process and interactions, directing them toward specific topics: the use of stories and proverbs as narrative tools; visualization tools like the four areas of body, achievement, contact, and fantasy application in groups; actual capacities to describe group processes and interaction pattern; the group process as a matter of treatment, connotation and contents; positive group psychotherapy moderated in a five steps process; positive group theory to understand the internal and external group dynamics will be presented; sociodynamics and psychodynamic descriptions of the upcoming dynamic in groups.